2002
DOI: 10.1080/0365034021000071837
|View full text |Cite
|
Sign up to set email alerts
|

The effect of zinc (Zn) application on uptake of cadmium (Cd) in some cereal species

Abstract: It is widely accepted that plants absorb more Cd when they suffer from Zn deficiency, as the Zn deficiency is a critical problem in the world. The effect of increased Cadmium (Cd) application (0 and 15 mg kg -l Cd) on growing and CA concentration in some cereal species was investigated at the increasing rate of Zinc (Zn) applications (0 and 15 mg kg -~ Zn). The experiment was carded out under greenhouse conditions using a Zn deficient soil. According to the results, that increased Cd applications severely redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…After joint application with Zn, the Pb content in the bean declined, however without significant differences (P>0.05, Figure 3). Many works [Adiloglu 2002;Adiloglu et al 2005;Angelova, Ivanov 2006] deal with interactions among heavy metals, especially the interactions between Cd and Zn. The mechanism of action and the final explanation of these relationships are not unified.…”
Section: Resultsmentioning
confidence: 99%
“…After joint application with Zn, the Pb content in the bean declined, however without significant differences (P>0.05, Figure 3). Many works [Adiloglu 2002;Adiloglu et al 2005;Angelova, Ivanov 2006] deal with interactions among heavy metals, especially the interactions between Cd and Zn. The mechanism of action and the final explanation of these relationships are not unified.…”
Section: Resultsmentioning
confidence: 99%
“…Another study showed that CdZn interactions are synergistic to each other and increasing the concentrations of Cd and Zn in soils could enhance the accumulation of these metals in crops 112. Adiloglu113 showed that Cd accumulation in plants is reduced with the application of Zn, and Cd accumulation is greater in Zn‐deficient soils. Qiu et al 47 proposed that increasing levels of Zn compete with Cd for the same membrane binding sites and transport systems and also limits Cd transport from phloem to grain.…”
Section: Essential Plant Nutrientsmentioning
confidence: 99%
“…The improvement of Zn nutritional status also reduces the uptake of harmful heavy metals, i.e. hinders their toxicity in plants, such as Cd [7]. According to Lin and Xing [8], there is a limited or no information available on the plant cell internalisation of NPs.…”
Section: Introductionmentioning
confidence: 98%